2015
DOI: 10.1111/joms.12118
|View full text |Cite
|
Sign up to set email alerts
|

On the Same Side of the Faultline: Inclusion in the Leader's Subgroup and Employee Performance

Abstract: Extending theory on faultlines and subgroups, we argue that faultlines splitting a team into homogeneous subgroups can have different effects on team members' individual performance, depending on different intra-subgroup processes. Specifically, we propose that the effect of faultline strength on individual performance depends on whether a team member's subgroup includes the team leader. Building on the notion of faultline triggers, we further propose that organizational crises exacerbate this interaction beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 96 publications
8
62
0
1
Order By: Relevance
“…Leaders have been argued to act as interpretative filters of organizational events (Luria, ) and have been found to influence the emergence of consensus in climate perceptions (González‐Romá & Peiró, ). Future research may aim at extending these findings by considering differentiated forms of leadership (e.g., leader–member exchange differentiation and differentiated individual‐focused transformational leadership) along with leaders' own attitudes toward diversity (Greer et al, ) or their subgroup membership (Meyer, Shemla, Li, & Wegge, ) as these factors may lead to systematic variations in the treatment of demographically (dis‐)similar followers. As for the consequences of demographic splits in diversity climate perceptions, future multilevel research may also consider individual‐level effects, as deviations from dominant diversity climate perceptions may have different implications for members of low‐ and high‐status groups.…”
Section: Discussionmentioning
confidence: 99%
“…Leaders have been argued to act as interpretative filters of organizational events (Luria, ) and have been found to influence the emergence of consensus in climate perceptions (González‐Romá & Peiró, ). Future research may aim at extending these findings by considering differentiated forms of leadership (e.g., leader–member exchange differentiation and differentiated individual‐focused transformational leadership) along with leaders' own attitudes toward diversity (Greer et al, ) or their subgroup membership (Meyer, Shemla, Li, & Wegge, ) as these factors may lead to systematic variations in the treatment of demographically (dis‐)similar followers. As for the consequences of demographic splits in diversity climate perceptions, future multilevel research may also consider individual‐level effects, as deviations from dominant diversity climate perceptions may have different implications for members of low‐ and high‐status groups.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, one study found that members of larger subgroups are more likely to exhibit social loafing behavior, especially if they displayed low levels of social competence (Meyer, Schermuly, & Kauffeld, 2016). Similarly, members of homogeneous subgroups that include the leader of the team perform better than members of leaderless subgroups if the organization faces a crisis (Meyer, Shemla, Li, & Wegge, 2015). These findings show that diversity-related processes can operate between the individual and the team level of analysis.…”
mentioning
confidence: 89%
“…A recent review of these contingencies (Guillaume et al, in press) identifies no less than six broad categories of moderators spanning multiple levels from the individual team member to the organization (strategy, unit design, human resource management practices, leadership, climate and culture, and individual differences among team members). Accordingly, there is a clear need for overarching theories integrating multiple levels of analysis, which is also evident in the fact that an increasing number of recent studies adopt multilevel frameworks (Joshi, in press;Joshi & Knight, 2015;Leslie, in press;Meyer et al, 2015;Richard, Stewart, McKay, & Sackett, in press). A microdynamic perspective is particularly necessary when considering temporal dynamics, which has been largely absent in diversity research (Cronin et al, 2011;Humphrey & Aime, 2014).…”
Section: The Need For a Microdynamic Perspective On The Diversity-permentioning
confidence: 99%
“…Somewhat in contrast, Meyer et al . () argue that individual performance in a team improves when the team leader is of the same subgroup. This might be extended to argue that clustering team members of the same subgroup together might improve overall team performance.…”
Section: Team Science Research Questions: a Proof‐of‐concept Of The Hmentioning
confidence: 99%